Clay Dispersed Styrene-co-Glycidyl Methacrylate Impregnated Kumpang Wood Polymer Nanocomposites: Impact on Mechanical and Morphological Properties - Md. Tipu, Sultan; Md. Rezaur, Rahman; Sinin, Hamdan; Chang, Josephine Hui Lai; Zainal Abidin, Talib (BioResources, 2016)
Physical, mechanical, and morphological properties of a clay dispersed styrene-co-glycidal methacrylate (ST-co-GMA) impregnated wood polymer nanocomposite (WPNC) were evaluated. The WPNC was characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), 3-point bending, free-vibration testing, and X-ray diffraction (XRD) measurements. The FT-IR results showed that the absorbance at 1730 cm−1 was increased for ST-co-GMA-clay-WPNC compared with other nanocomposites and the raw material. The XRD results revealed that crystallinity index and d-spacing were increased compared to raw wood. The SEM results showed that ST-co-GMA-clay-WPNC had a smoother surface than other nanocomposites and raw wood. The modulus of elasticity (MOE), modulus of rupture (MOR), and dynamic Young’s moduli (Ed) of WPNCs were considerably increased compared to wood polymer composites (WPCs) and raw wood. The raw wood exhibited a higher water uptake (WU) than WPNCs and WPCs.